Comparison of Physical Activity in Fertile and Infertile Couples in Kermanshah, Iran during 2013 - Khosrorad, Tahereh; Dolatian, mahrokh; Riazi, Hedyeh; Mahmoodi, Zohreh; Shahsavari, Soodeh; Yadegari, Mahtab (Advances in Nursing & Midwifery, 2016)
Abstract: Background and aim Infertility is a major reproductive health problem that affect 10%-15% of couples. According to the World Health Organization, there are currently 50-80 million infertile couples in the world. Physical activity is a life style factor with possible positive or negative effects on reproductive. The aim of this study was to compare the physical activity of fertile and infertile couples in Kermanshah, Iran during 2013. Materials and Methods This was a descriptive comparative study. The case group consisted of 118 infertile couples attending Motazedi Infertility Center. One hundred and eight fertile couple attending to six public health centers in Kermanshah, Iran, were the controls. The sampling method was convenience sampling. Data were collected by a questionnaire. The questionnaire was consisted of two section. The first section was demographic and fertility characteristics and the second section was international physical activity questionnaire. The data is presented by descriptive statistics and analyzed with logistic regression, independent t-test, chi-square, and gamma tests using SPSS v16. Results The result of this study showed that the majority of fertile women(86.1%), infertile women(73.1%), fertile men(87%) and infertile men(96.3%) had moderate level of physical activity. There was a significant difference between fertile and infertile men and women in terms of physical activity. The fertile and infertile couples, also, have significant difference in physical activity(P<0/05). Conclusions Given the importance of physical activity on reproductive health and significant difference of physical activity between fertile and infertile couples in this study, it seems that more attention should be paid to lifestyle behaviors, especially in infertile couples. Keywords Life Style; Physical Activity; Fertility, Iran